1995
DOI: 10.1080/09540129550126722
|View full text |Cite
|
Sign up to set email alerts
|

A measure of knowledge and confidence in relation to HIV and AIDS: Reliability and validity

Abstract: Knowledge of HIV and AIDS is widely seen as an important determinant of anxiety about such infection in health care workers. However, existing measures of this knowledge suffer from a number of methodological problems and few demonstrate adequate reliability and validity. This paper documents the development of a new measure detailing its reliability and validity. Knowledge, and also confidence in knowledge, were assessed across seven domains of relevant information (e.g. epidemiology, personal risk, symptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Such a measure would comprise a self‐report of knowledge, as opposed to a knowledge test. Research in other areas, however, casts doubt on such a goal, showing that the association between what people know and their estimates of this knowledge is positive but not perfect, with people tending to overestimate how much they know 28,29 . It may, however, be possible to generate a template of information about any screening test that is a prerequisite to informed choice.…”
Section: Discussionmentioning
confidence: 99%
“…Such a measure would comprise a self‐report of knowledge, as opposed to a knowledge test. Research in other areas, however, casts doubt on such a goal, showing that the association between what people know and their estimates of this knowledge is positive but not perfect, with people tending to overestimate how much they know 28,29 . It may, however, be possible to generate a template of information about any screening test that is a prerequisite to informed choice.…”
Section: Discussionmentioning
confidence: 99%
“…18-20 Each of these studies has found that people's perceptions of their knowledge about a specific topic tend to be higher than their actual knowledge levels. This tendency to overestimate one's knowledge underscores the importance of knowledge measures that ask questions about specific facts, rather than asking only how informed a person feels.…”
Section: Discussionmentioning
confidence: 99%
“…These items were comprised of one symptomatology question (from Ferguson et al, 1995), with the remaining items concerned with HIV transmission and misconceptions taken from the ''AIDS Risk Knowledge Questionnaire'' (Kelly et al, 1989). For this sample, the coefficient alpha was .43 and the mean inter-item correlation was .10.…”
Section: Methodsmentioning
confidence: 99%